ANALISA PENGARUH LEADERSHIP STYLE TERHADAP FIRM PERFORMANCE MELALUI LEARNING ORGANIZATION DAN EMPLOYEE SATISFACTION PADA PERUSAHAAN SEKTOR MANUFAKTUR DI SURABAYA - Yemima Yulia; Saarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of leadership style to learning organization, leadership style to employee’s satisfaction, learning organization to firm’s performance, employee’s satisfaction to firm’s performance, leadership style to firm’s performance, and learning organization to employee’s satisfaction on manufacturing companies in Surabaya. This study used quantitative approach and the data were obtained through the distribution of questionnaire to manufacturing firm in Surabaya and processed by using PLS software. This study showed that there was a positive and significant relationship of leadership style to learning organization, leadership style to employee’s satisfaction, learning organization to firm’s performance, employee’s satisfaction to firm’s performance, leadership style to firm’s performance, and learning organization to employee’s satisfaction on manufacturing companies in Surabaya.